Exploring genetic diversity and genomic inbreeding across local beef cattle breeds - G. Gomez Proto; E. Mancin; A. Quaglia; F. Sbarra; R. Mantovani; C. Sartori (Animal, 2025)
Beef cattle breeds from Central and Southern Italy, such as Marchigiana, Chianina, Romagnola, Maremmana, and Podolica, represent a unique genetic resource shaped by centuries of natural and artificial selection. Their origin, partly linked to the Podolian group, remains debated, while their adaptation to diverse environments and close association with regional economies enhance their zootechnical and cultural value. Despite their importance, comprehensive assessments of their genomic diversity are still limited, especially in an international context where preserving local breeds is crucial to maintain global biodiversity and resilience in livestock systems. This study investigates population structure, inbreeding, selection signatures, and effective population size using medium-density single-nucleotide polymorphism genotypes. Multivariate and clustering approaches confirmed clear genetic differentiation among breeds, with Chianina and Romagnola being the most divergent, in line with their intensive selection history. In contrast, Maremmana and Podolica displayed shared ancestral components, reflecting their adaptation to extensive and marginal environments. Pairwise Fst values supported these patterns of divergence, while the phylogenetic tree grouped specialised beef breeds (Marchigiana, Chianina, Romagnola) separately from the more rustic ones (Maremmana and Podolica). Historical Ne trajectories revealed long-term contraction in Chianina and Romagnola, whereas Podolica maintained higher Ne over time. Runs of homozygosity (ROH) were used to estimate inbreeding coefficients (FROH) and to distinguish ancient (ROH ≤ 4 Mb) from recent inbreeding (ROH ≥ 8 Mb). Chianina exhibited the highest FROH values, mainly composed of shorter ROH, suggesting older inbreeding episodes. ROH islands were detected on BTA5 and BTA6 and included genes such as FGF5, RAB21, KRT71, and DCAF16, which are linked to coat characteristics, growth, and environmental adaptation. Gene Ontology enrichment analyses indicated their involvement in relevant biological functions. Overall, this study provides a comprehensive genomic characterisation of five Italian beef cattle breeds, emphasising their differentiation, demographic history, and signatures of selection. These findings enhance the understanding of local genetic resources and contribute to broader strategies for the conservation and sustainable use of animal biodiversity in the face of global challenges.